Renal Amyloidosis in Pediatric Autoinflammatory Syndromes: Subclinical Onset, Early Biomarkers, and Clues for Timely Characterization and Interventions - Naqiya Arsiwala; Donato Rigante (Journal of Clinical Medicine, 2026)
Background/Objectives: Autoinflammatory syndromes are defined by episodes of recurrent fever driven by innate immune dysregulation, yet their long-term organ consequences remain largely underestimated, mostly in children. Renal AA amyloidosis represents the most perilous complication of sustained, even subclinical, inflammation, capable of progressing silently to irreversible renal failure. In pediatric cohorts, the interval between autoinflammatory disease onset and amyloidosis diagnosis spans nearly a decade, an actionable window that current surveillance frameworks have not adequately addressed. This review examines the pathophysiological continuum linking chronic cytokine overproduction to renal amyloid deposition in children with autoinflammatory syndromes, evaluates emerging subclinical biomarkers of early renal injury, identifies relevant diagnostic pitfalls, and proposes a structured renal surveillance framework for at-risk pediatric populations. Materials and Methods: This comprehensive review has been conducted analyzing studies reporting renal outcomes, biomarker data, or therapeutic interventions in pediatric patients with monogenic or polygenic autoinflammatory conditions. No date restriction was applied, with emphasis placed on publications from 2015 onward reflecting contemporary treatments and diagnostic standards. Results: An overproduction of interleukin (IL)-1β and IL-6 drives serum amyloid-A accumulation that may persist measurably during intercritical periods, preceding overt proteinuria by years in most young patients with autoinflammatory syndromes. Urinary neutrophil gelatinase-associated lipocalin (NGAL) is significantly elevated in attack-free children with familial Mediterranean fever (FMF) compared to healthy controls, representing an early and sensitive marker of tubular stress. Shear wave elastography has demonstrated measurable increases in renal tissue stiffness in pediatric FMF patients, correlating with subclinical inflammatory activity. Critically, nutcracker syndrome has emerged as the leading cause of proteinuria in colchicine-treated FMF cohorts, accounting for up to 67.5% of proteinuria cases and representing a clinically significant confounder. IL-1 inhibition with either anakinra or canakinumab has demonstrated histological regression of established amyloid deposits in different cohorts of pediatric patients, reinforcing the potential therapeutic value of earlier identification and intervention before overt irreversible glomerular damage comes out. Conclusions: Renal amyloidosis in autoinflammatory syndromes is a plausibly preventable outcome when subclinical injury is identified and treated within the pre-amyloid window in the pediatric age. Conventional reliance on ‘proteinuria’ as the primary surveillance threshold is potentially misleading. A biomarker-guided monitoring approach incorporating serum amyloid-A, urinary NGAL, and renal elastography might offer a clinically actionable pathway toward earlier nephrology referral and targeted IL-1 blockade, with the potential to improve renal prognosis of these children.